2020
DOI: 10.7717/peerj.8230
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate size influences the impact of inorganic nitrogen deposition on soil nitrification in an alpine meadow of the Qinghai–Tibet Plateau

Abstract: Background Ammonium (NH4+) and nitrate (NO3−) are two inorganic forms of nitrogen (N) that are deposited from the atmosphere into soil systems. As the substrate and product of soil nitrification, these two forms of inorganic nitrogen will affect or be affected by the soil net nitrification rate (Nr). Our knowledge regarding soil nitrification is mainly derived from studies with bulk soil. However, soil is composed of different aggregate fractions, which may have an important impact on Nr. Methods In 2017, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The average annual temperature is −0.45°C, with extremes of −29°C and 27°C distributed between January and July per year. The soil is clay-loam and classified as Mat-Gryic-Cambisol (Li et al, 2020 ). The main species of plants in this study area include Leymus secalinus, Stipa purpurea, Poa pratensis, Kobresia humilis, Melissitus ruthenica, Potentilla chinensis , and Artemisia frigida .…”
Section: Methodsmentioning
confidence: 99%
“…The average annual temperature is −0.45°C, with extremes of −29°C and 27°C distributed between January and July per year. The soil is clay-loam and classified as Mat-Gryic-Cambisol (Li et al, 2020 ). The main species of plants in this study area include Leymus secalinus, Stipa purpurea, Poa pratensis, Kobresia humilis, Melissitus ruthenica, Potentilla chinensis , and Artemisia frigida .…”
Section: Methodsmentioning
confidence: 99%
“…Third, in the present study higher levels of microbial biomass were evident in smaller aggregates. Higher microbial load in microaggregate has been associated with increased levels of activities for hydrolases including urease, nitrate reductase, L-glutaminase, and beta-glucosidase, thus contributing to elevated rates of N mineralization such that following N input (Khorsandi and Nourbakhsh, 2007;Li et al, 2021), such N mineralization increased. The results indicated the highest net N conversion and nitrification rates in microaggregates under N90 treatment conditions (Figure 5B), indicating that high N input can raise effective soil N concentrations and intensify mineral N loss, reducing the soil's N fixation capacity (Fang et al, 2009).…”
Section: Aggregate Structural Properties Reduce Soc and Total N Miner...mentioning
confidence: 99%
“…Conversely, Tao and Song (2014) pointed out that nitrogen deposition notably inhibited carbon mineralization in macroaggregates, but enhanced it in microaggregates. Furthermore, Li et al (2020) reported that the rise in nitrogen mineralization due to nitrogen addition was mainly attributed to microaggregates. The addition of N increases the uncertainty faced by C and N mineralization in aggregates.…”
Section: Introductionmentioning
confidence: 99%